Immune Checkpoint Inhibitor Therapy for Bone Metastases: Specific Microenvironment and Current Situation - Chang Liu; Miao Wang; Changli Xu; Bo Li; Juxiang Chen; Jianchun Chen; Zhiwei Wang (Journal of Immunology Research)
The treatment of bone metastases is a thorny issue. Immunotherapy may be one of the few hopes for patients with unresectable bone metastases. Immune checkpoint inhibitors are the most commonly used immunotherapy drugs currently. In this review, the characteristics and interaction of bone metastases and their immune microenvironment were systematically discussed, and the relevant research progress of the immunological mechanism of tumor bone metastasis was reviewed. On this basis, we expounded the clinical application of immune checkpoint inhibitors for bone metastasis of common tumors, including non-small-cell lung cancer, renal cell carcinoma, prostate cancer, melanoma, and breast cancer. Then, the deficiencies and limitations in current researches were summarized. In-depth basic research on bone metastases and optimization of clinical treatment is needed.